The current novel drug delivery system (natural and chemical composites) in dental infections for antibiotics resistance: a narrative review: The current novel drug delivery system in dental infections - Tahmasebi, Elahe; Kaboudanian Ardestani, Ali; Hassani, Zahra; Alam, Mostafa; Abbasi, Kamyar; Kahrizi, Sepehr; Madihi, Negar; Abbasiparashkouh, Zahra; Mohammadi, Arman; Shahab, Pooria; Khayatan, Danial; Yazdanian, Mohsen (Cellular and Molecular Biology, 2022)
A mouth infection can also affect the teeth, the mouth tissues, and any other areas involved in the mouth. Biofilms formed by bacteria are the primary cause of mouth infections and other infectious diseases caused by bacteria. The most common dental problem is an infection or disease within the mouth. The term chronic infection is sometimes used to describe this type of problem. There is also the possibility that these discomforts may occur due to the presence of bacteria in plaque, which is responsible for causing inflammation throughout the body as a result of bacterial infection in the mouth. In many cases, antibiotics serve as a first-line treatment for mouth infections, especially those caused by bacteria, most commonly treated by antibiotics. It is common for antibiotics to be used orally, and they are absorbed into the body through their metabolism in the liver and kidneys. Antibiotic resistance, which is primarily caused by misuse and overuse of antibiotics, is also one of the most significant public health crises of the 21st century. With the help of new drug delivery systems, antibacterial resistance can be decreased in humans to maintain the effectiveness of antibiotics when they are used more frequently. By directly delivering antibiotics to damaged tissues and reducing undesirable side effects when administered systemically, antibiotic delivery systems enhance the efficiency of antibiotics in specific zones. Furthermore, several new delivery systems are being explored in an attempt to improve pharmacokinetics and pharmacodynamics, reduce bacterial resistance, and decrease dose times. As a result, antibiotics were delivered to tissues and biological fluids using an innovative delivery system. Research on some of the most prevalent dental diseases provides updates on antibiotic delivery systems that reduce antibiotic resistance. This review overviews oral infectious diseases, antibiotics effects, and the different delivery systems of these therapeutic approaches.